Influencia de distintas densidades de siembra al voleo sobre la calidad molinera en la línea promisora L-38 de arroz (Oryza sp) - Franco Hidalgo, Anthony Alfredo (2025)
This research evaluates the influence of different broadcast seeding densities on milling quality in the promising L-38 rice line and compares it with the commercial SFL-11 variety in Babahoyo, Ecuador. This study arose from the need to optimize agronomic practices that can improve the competitiveness of local rice, considering that planting densities can directly impact parameters such as milling yield, grain integrity, and physicochemical properties. A completely randomized design (CRD) was used, analyzing six planting densities (43 to 80 kg/ha) and using two cultivars (L-38 and SFL-11), measuring and comparing variables such as hull weight, brown rice, polishing, dustiness, white center, whiteness, amylose content, and protein. This study evaluated how planting densities can affect the milling quality of the L-38 and SFL-11 cultivars in the Babahoyo area.It was observed that the interaction between rice variety and planting density is important, especially in parameters such as the amount of seed dust and the presence of white centers in the grain. The L-38 variety demonstrated an optimal balance between quality and yield when planted at moderate densities, between 58 and 72 kilograms of seed per hectare. It was concluded that the L-38 variety surpasses SFL-11 in certain traits and equals it in others in quality, confirming findings previously made on improved rice lines